2016
DOI: 10.1002/ddr.21300
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive Interactions Between Meloxicam and Gabapentin in Neuropathic Pain Depend on the Ratio used in Combination in Rats

Abstract: Preclinical Research Neuropathic pain is particularly difficult to treat because of its diverse etiologies and underlying pathophysiological mechanisms. Drug combinations have been proposed to effectively treat some neuropathies. In the present study the interaction of five combinations of meloxicam and gabapentin, were studied to assess the possible synergistic antinociceptive response in neuropathic pain using the von Frey and acetone tests in rat models. Coadministration of meloxicam and gabapentin increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…The evidence is related to the use of traditional drugs for the treatment of this type of pain such as gabapentinoids in combination with opioid drugs, such as morphine, oxycodone and tapentadol, or with antidepressants, such as duloxetine, as well as the combination of antidepressants with opioid drugs (Chaparro, et al, 2012; Christoph, De Vry, Schiene, Tallarida, & Tzschentke, 2011; De la O‐Arciniega et al, 2009; García‐Martínez et al, 2016). Some studies have used NSAIDs with antiepileptic or opioid drugs that showed promising results at the preclinical level (Abass, Mosbah, Rizk, Karrouf, & Zaghloul, 2014; Espinosa‐Juárez, Jaramillo‐Morales, Corona‐Ramos, Medina‐López, & López‐Muñoz, 2016). All these combinations tend to induce additive or synergistic effects; however, in these works, it was not possible to determine which combinations could produce the best effect.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence is related to the use of traditional drugs for the treatment of this type of pain such as gabapentinoids in combination with opioid drugs, such as morphine, oxycodone and tapentadol, or with antidepressants, such as duloxetine, as well as the combination of antidepressants with opioid drugs (Chaparro, et al, 2012; Christoph, De Vry, Schiene, Tallarida, & Tzschentke, 2011; De la O‐Arciniega et al, 2009; García‐Martínez et al, 2016). Some studies have used NSAIDs with antiepileptic or opioid drugs that showed promising results at the preclinical level (Abass, Mosbah, Rizk, Karrouf, & Zaghloul, 2014; Espinosa‐Juárez, Jaramillo‐Morales, Corona‐Ramos, Medina‐López, & López‐Muñoz, 2016). All these combinations tend to induce additive or synergistic effects; however, in these works, it was not possible to determine which combinations could produce the best effect.…”
Section: Discussionmentioning
confidence: 99%
“…Gabapentin injected intradermally into the hindpaw can induce analgesia [Todorovic et al, ] and gabapentin is also effective in acute and chronic models of inflammatory pain [Singh et al, ; Heughan and Sawynok et al, ; Hurley et al, ] and reverses allodynia and hyperalgesia induced by 1% formalin [Salinas‐Abarca et al, ]. Gabapentin can decrease allodynia induced by nerve lesions in a neuropathic rat model [Chen et al, ; Field et al, ; Mixcoatl‐Zecuatl et al, ; Yamama et al, ; Miranda et al, ; Corona‐Ramos et al, ; Espinosa‐Juárez et al, ]. The antiallodynic effect of gabapentin may result from binding to the α2δ1 subunit of L‐type voltage‐dependent Ca 2+ channels [Gee et al, ] although it could activate other targets.…”
Section: Discussionmentioning
confidence: 99%
“…For our knowledge, this study shows for the first time the synergistic interaction of these two drugs. However, gabapentin has been co‐administered with (1) NSAIDs like naproxen [Hurley et al, ], meloxicam [Espinosa‐Juárez et al, ], ibuprofen [Yoon and Yaksh, ], diclofenac [Picazo et al, ] and metamizol [Ortega‐Varela et al, ]. (2) antidepressants like venlafaxine [Rode et al, ], nortriptyline [Miranda et al, ], and amitriptyline [Heughan and Sawynok, ].…”
Section: Discussionmentioning
confidence: 99%
“…5, в). В эксперименте было показано, что мелоксикам усиливал анальгетический эффект агониста ГАМК-рецепторов габапентина у крыс с моделью невропатической боли [19]. Заключение.…”
Section: Conclusion the Chemoreactomе Analysisunclassified